Australia - a criminal justice system weighted against Aboriginal people - Amnesty International (Broadway [N.S.W.] : Australian Section Office, 1993)
Annotation pending.
Keywords: Discrimination in criminal justice administration -- Australia; Prisoners, Aboriginal Australian; Prisoners, Aboriginal Australian -- Mortality; Aboriginal Australians -- Criminal justice system; Prisons and race relations -- Australia; Police -- Complaints against -- Australia; Detention of persons -- Australia; Law - Legal system; Law enforcement - Prisons - Prisoners; Law enforcement - Custody; Law enforcement - Police; Law enforcement - Prisons; Law enforcement - Criminal law and procedure - Juvenile justice; Mparntwe / Alice Springs (South Central NT SF53-14)